Three-dimensional deformation mapping of Mode I interlaminar crack extension in particle-toughened interlayers. (15th January 2016) - Borstnar, G.; Gillard, F.; Mavrogordato, M.N.; Sinclair, I.; Spearing, S.M.
Abstract: This paper presents the first use of Digital Volume Correlation (DVC) on Carbon Fibre Reinforced Plastics (CFRPs) to quantify the strain fields ahead of a Mode I delamination. DVC is a relatively novel tool that can be used to measure displacements and strains occurring inside materials under load. In conjunction with Computed Tomography (CT), the technique has been applied to porous materials, with results providing strain data for validation of Finite Element (FE) models. However, the application of the technique to laminated materials has been limited, with studies often requiring fiducial markings required for volume correlation. In this work, crack propagation steps were captured at a 325 nm voxel resolution using Synchrotron Radiation Computed Tomography (SRCT). The material systems investigated featured different crack bridging mechanisms such as; particle-bridges, resin ligaments, and fibre-bridges. An assessment of noise and sub-volume size on the strain measurement determined that the optimal sub-volume size was 150 voxels with 50% overlap. This provided a spatial resolution of 48.8 μm for strain and a corresponding strain resolution ranging between 220 and 690 με for the repeated reference scans. A rigid body translation study confirmed that specimen movements perpendicular to the fibre orientation support the 'real' physical displacements. However, along the fibre direction, the correlation was poor, with correct displacements being detected only within the particle-toughened interlayers. The study demonstrates that strain measurements can be made perpendicular to the fibre direction across the interlayer, which could be used to validate future FE models of these poorly understood particle-toughened interlayers. Graphical abstract: